Bonus Compensation and Real Earnings Management: Audit Committee Effectiveness as Moderation Variable - Suhardjo Suhardjo; Nicholas Renaldo; Andi Andi; Sudarno Sudarno; Marice Br. Hutahuruk; Suharti Suharti; Kristy Veronica (STIE Binaniaga, 2022)
This study analyzes the effect of bonus compensation on real earnings management, with the audit committee effectiveness as a moderating variable in manufacturing companies in Indonesia. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2020. The research sample was selected by the purposive sampling method. Hypothesis testing is done by using panel data regression and Moderated Regression Analysis (MRA). The results showed that bonus compensation had a positive effect on real earnings management, while the effectiveness of the audit committee did not weaken the effect of bonus compensation on real earnings management. The findings of this study provide an overview to the company's stakeholders that bonus compensation is one of the factors that motivates company management to practice earnings management, especially earnings management related to the company's real activities. In addition, this study also provides an overview of the effectiveness of the implementation of corporate governance mechanisms in the sample companies, in particular the ineffectiveness of the supervisory function related to earnings management practices carried out by the audit committee.